Zebrafish larvae lose vision at night - Emran, Farida (National Academy of Sciences, 2010)
Darkness serves as a stimulus for vertebrate photoreceptors; they are actively depolarized in the dark and hyperpolarize in the light. Here, we show that larval zebrafish essentially turn off their visual system at night when they are not active. Electroretinograms recorded from larval zebrafish show large differences between day and night; the responses are normal in amplitude throughout the day but are almost absent after several hours of darkness at night. Behavioral testing also shows that larval zebrafish become unresponsive to visual stimuli at night. This phenomenon is largely circadian driven as fish show similar dramatic changes in visual responsiveness when maintained in continuous darkness, although light exposure at night partially restores the responses. Visual responsiveness is decreased at night by at least two mechanisms: photoreceptor outer segment activity decreases and synaptic ribbons in cone pedicles disassemble.